Ibnu Miskawaih dan Tradisi Pendidikan Anak Usia Dini - Birroh, Nailul (Prodi Pendidikan Agama Islam IAINU Kebumen, 2025)
This study aims to examine the relevance of Ibn Miskawayh’s thought in early childhood education, particularly in shaping children's character in the digital age. Amidst the challenges of globalization and rapid technological advancements, early character education has become increasingly urgent. Through a literature review focusing on Ibn Miskawayh’s seminal work Tahzib al-Akhlaq, this research reveals that his perspectives on ethics, the human soul, and educational methods are highly applicable to contemporary child education. Ibn Miskawayh emphasized the importance of habituation, guidance, and role modeling in the character-building process. His balanced integration of Islamic teachings and philosophical reasoning provides a solid foundation for value-based character education. The findings show that his educational principles are highly relevant to early childhood education institutions (PAUD) in strengthening children’s character development in modern times.